Qu’est le quilombo aujourd’hui devenu ? De la catégorie coloniale au concept anthropologique - Véronique Boyer (Journal de la Société des Américanistes)
The construction of the quilombo object : from colonial category to anthropological concept. After the enactment of the article 68 of the 1988 Brazilian Constitution, anthropology became interested in the emergence of a quilombola identity in a society where the quilombo is supposed to belong to the past. Researchers intend to submit the old notion of quilombo to a process of evaluating its semantics (« re-semantization »). They aim to transform it into a concept enabling to understand the reality of new forms of political mobilization. To identify and understand the singularity of groups called Quilombola, these authors question the nature of their characteristics and the areas of social, cultural and political life where it is possible to comprehend them. It is therefore necessary to identify what is common to different approaches, but also what distinguishes them by pointing out how the reflection and discussion to update the definition of the concept of quilombola was conducted, from which assumptions, with which terms and according to which perspectives